Could Gamification Designs Enhance Online Learning Through Personalization? Lessons from a Field Experiment - Leung, Alvin Chung Man; Santhanam, Radhika; Kwok, Ron Chi-Wai; Yue, Wei Thoo (Information Systems Research, 2023)
Online learning is of growing importance to institutions and learners, and the COVID-19 pandemic has underscored its importance even more. Because learner autonomy is relatively high in these online environments, they must engage in self-regulated learning processes to achieve successful learning outcomes, but studies show that most learners are not able to do so. Hence, in this longitudinal field experiment, using a massively open online course (MOOCs), a type of online learning environment, we investigate whether gamified interventions through the learning platform can foster learners to engage in self-regulated learning processes and improve their learning outcomes. We find that gamification interventions are indeed useful, but for these gamification interventions to succeed, they must be designed to provide personalized feedback to learners that match with their learning goal-orientation. Overall, our findings point to the fact that gamification designs in online learning platforms can enhance learners’ engagement and learning outcomes, but they must be personalized. A one-size-fits-all approach to gamification design in online learning just does not work and may even backfire to reduce the engagement of some learners.